(untitled) (International Educators Conference, 2025)
This article analyzes strategies for developing technical creativity using information and communication technologies (ICT). In the modern educational process, ICT plays a crucial role in enhancing students’ ability to think creatively and solve technical problems. The integration of digital tools such as 3D modeling, virtual laboratories, artificial intelligence, and simulation technologies allows students to apply innovative approaches in engineering and technical education.